Assessment of Stress Raiser Factor Using Finite Element Solvers - Fondjo, A.A.; Dzogbewu, T.C. (Universal Journal of Mechanical Engineering, 2019)
The stress raisers factor around circular holes in a plate exposed to uniform tensile load at the edges has been studied using Finite Element Analysis solvers. The effect of mesh quality on stress raisers factor, the maximum Von Mises stresses, the computing time, and the percentage error has been examined. 4 Node Quadrilateral Element and 8 Node Quadrilateral Element were utilized respectively as first-order component (4NQE) and higher-order component (8NQE) to assess the maximum Von Mises stress and the numerical stress raiser factor (Kn) at various mesh sizes. The maximum Von Mises stress and the stress raiser factor were determined using the following finite element solvers: ABAQUS, ANSYS, CATIA, STRAND 7, ALGOR, COSMOS/M, and FEMAP. The estimations of the numerical stress raiser factor (Kn) were compared with the theoretical stress raiser factor (Kt). There were discrepancies observed between the maximum Von Mises stresses of the FEA solvers.
Published Article
Keywords: Finite Element Analysis; Stress Raiser Factors; Von Mises Stress; Mesh Size; Geometric Discontinuities